Development and control of an assistive robotic glove - Seow, Wen Xuan (Nanyang Technological University, 2020)
Stroke is a medical condition that affects a high percentage of the population in the world. The risk of suffering from a stroke increases with age, which makes the ageing population around the world a major factor in the increase in the stroke cases. One of the most common consequences of suffering from a stroke is the impairment of upper limb functionality. There is therefore a need for a device that would assist such patients in Activities of Daily Living (ADLs), to allow them to continue living their lives with as little hindrance from the impairment as possible. Although there are designs and products already out there to fulfill this purpose, none of the designs are easily accessible to the average consumer and usually incorporate an actuation system that would make using it on a daily basis impossible. Such designs are also usually heavy, loud and bulky. Thus, this project focuses on creating an assistive glove to replace hand gripping function, which is simple to build, rugged and could be used on a daily basis. Research was done on the other existing types of gloves in the market and a design direction was decided upon. A single actuator mechanical linkage design was chosen and iterated until an acceptable performance and functionality was achieved. The performance of the glove was measured with force sensors, a standardized hand functionality test (Action Research Arm Test), and the types of ADLs that the glove could allow the user to achieve. In the end, the project met its objectives of completing basic ADLs using only a pinch grip while a cylinder grip was only partially achieved. Recommendations were then made for the further development of the design at the end of the report.